Investigating Different Effects of Divided Doses of Sucrose 24% Compared to Single Dose for Pain Prophylaxis Before Heel Stick in Term and Preterm Neonates - Maryam Nakhshab; Mahkameh Soltani; Vajiheh Ghaffari; Roya Farhadi; Majid Saeedi; Mohammadreza Rafati (Mazandaran University of Medical Sciences, 2023)
Background and Objectives: Neonates frequently experience acute pain from numerous procedures during routine patient care at the intensive care units. Oral sweet solutions (sucrose) are used as analgesics during minor procedures. According to the mechanism of the sucrose effect, this question was raised whether there is a relationship between the way it is consumed and the amount of pain reduction. This study aims to compare single vs divided doses of sucrose 24% for prophylaxis of pain before heel stick in neonates. Methods: In this randomized double-blind controlled clinical trial, hospitalized newborns requiring heel lance were enrolled and randomly assigned to receive sucrose 24% as a single dose at 2 min or three divided doses at 2, 1.5, and 1 min before the procedure. To accurately record the incident, the video of the babies was recorded during the procedures. The changes in pain parameters were evaluated to determine sucrose's analgesic effect using a premature infant pain profile-revised scale. Results: A total of 116 neonates were analyzed. Divided doses of sucrose decreased the pain score equally in term and preterm neonates (P=0.45). In contrast, the single dose method meaningfully reduced pain scores only in term neonates compared to preterm neonates (P=0.01). In the preterm infants' group, the mean premature infant pain profile-revised scores were significantly decreased in the divided dose method (P=0.016). Conclusion: The divided dose of sucrose was more effective than the single dose in both term and preterm infants. The single-dose method was more effective in term compared to preterm neonates. Administration of sucrose as a divided dose may be a more effective strategy for reducing pain in preterm neonates.